Caregiving burden and psychiatric morbidity in spouses of persons with mild cognitive impairment - Garand, Linda (2005)
BACKGROUND: While the deleterious psychosocial and mental health effects of dementia caregiving are firmly established, very little is known about the burdens or psychiatric outcomes of providing care to a spouse with less severe cognitive impairment, such as mild cognitive impairment (MCI). We characterized the nature and level of caregiver burden and psychiatric morbidity in spouses of persons diagnosed with MCI. METHODS: Interview assessments were completed on a cohort of 27 spouses of persons with a recent diagnosis of MCI. Patient medical records were reviewed to collect information regarding the MCI patient’s medical history. RESULTS: Respondents endorsed elevated levels of both task-related responsibilities and subjective caregiver burden. Depression and anxiety symptom levels also showed some elevations. Measures of caregiver burden were significantly associated with depression and anxiety levels. In particular, even after controlling for demographic risk factors for distress, nursing task burden was correlated with elevated depressive symptoms, and greater lifestyle constraints were correlated with higher anxiety levels. CONCLUSION: Although caregiver burden and psychiatric morbidity levels were lower than those typically observed in family dementia caregiving samples, our findings suggest that MCI caregivers have already begun to experience distress in association with elevated caregiving burden. These individuals may be ideal targets for selective preventive interventions to maximize their psychological well-being as caregiving burdens related to their spouses’ cognitive impairment increase.